2014
DOI: 10.1021/es501224b
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Patterns of Brominated, Chlorinated, and Phosphorus Flame Retardants with Particle Size in Indoor and Outdoor Dust and Implications for Human Exposure

Abstract: Dust samples were collected in Beijing, China, from four different indoor microenvironments (office, hotel, kindergarten, and student dormitory) and one outdoor (road dust) microenvironment. These five composite samples were fractionated into 13 sequential size fractions and an individual fraction of <50 μm for further analysis. In the fractions of <50 μm, nine phosphorus flame retardants (∑PFRs), four novel brominated flame retardants (∑NBFRs), and two Dechlorane Plus isomers (DPs) showed the highest concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(107 citation statements)
references
References 54 publications
5
99
2
1
Order By: Relevance
“…In the indoor dust in Beijing, China, the highest DP levels were found in kindergarten dust (231 ng g −1 ), which was even higher than in house dust from Guanzhou, China (mean 18.9 ng g −1 ) (Cao et al, 2014). A regular distribution pattern of DP in dust with particle size was also observed with stronger enrichment on fine particles than coarse particles, implying a potential human exposure to this chemical (Cao et al, 2014). In air, Ren et al (2008) investigated DP across 97 Chinese urban and rural sites by using PUF disk passive air samplers, and found that DP concentration in urban centers (mean value 15.6 ± 15.1 pg m − 3 ) was approximately 5 times greater than those measured in rural areas (3.5 ± 5.6 pg m −3 ).…”
Section: Urban/industrial Activitymentioning
confidence: 82%
See 1 more Smart Citation
“…In the indoor dust in Beijing, China, the highest DP levels were found in kindergarten dust (231 ng g −1 ), which was even higher than in house dust from Guanzhou, China (mean 18.9 ng g −1 ) (Cao et al, 2014). A regular distribution pattern of DP in dust with particle size was also observed with stronger enrichment on fine particles than coarse particles, implying a potential human exposure to this chemical (Cao et al, 2014). In air, Ren et al (2008) investigated DP across 97 Chinese urban and rural sites by using PUF disk passive air samplers, and found that DP concentration in urban centers (mean value 15.6 ± 15.1 pg m − 3 ) was approximately 5 times greater than those measured in rural areas (3.5 ± 5.6 pg m −3 ).…”
Section: Urban/industrial Activitymentioning
confidence: 82%
“…In the indoor dust from different microenvironments (i.e., home, workplace and car) in the Greater Cairo region, Egypt, both the syn-and anti-isomers were detected in 100% of the car dust samples reaching 4.94 and 5.65 ng g −1 , respectively (Hassan and Shoeib, 2015). In the indoor dust in Beijing, China, the highest DP levels were found in kindergarten dust (231 ng g −1 ), which was even higher than in house dust from Guanzhou, China (mean 18.9 ng g −1 ) (Cao et al, 2014). A regular distribution pattern of DP in dust with particle size was also observed with stronger enrichment on fine particles than coarse particles, implying a potential human exposure to this chemical (Cao et al, 2014).…”
Section: Urban/industrial Activitymentioning
confidence: 93%
“…In addition, high levels and detection frequency of OPEs have been observed in outdoor environment, including air particle matters (M€ oller et al, 2012;Salamova et al, 2014aSalamova et al, , 2014b and dust (Cao et al, 2014). It is probable that these pollutants in the outdoor air and dust are released into rivers along with wet deposition (rainfall) in the summer.…”
Section: Seasonal Variationmentioning
confidence: 99%
“…Exposure to EH-TBB is essentially ubiquitous due to its use in polyurethane foams and subsequent presence in house dust (Al-Omran and Harrad, 2016;Cao et al, 2014;Carignan et al, 2013;Harrad et al, 2010;Qi et al, 2014;Stapleton et al, 2014). A majority of systemic exposure to EH-TBB is expected to result from ingestion of dust, with upper range estimates of 0.2-0.4 ng EH-TBB/g dust/kg body weight (Ali et al, 2012;Al-Omran and Harrad, 2016).…”
mentioning
confidence: 99%